2011
DOI: 10.1002/ps.2144
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of spinosad with predaceous mites (Acari) used to control Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae)

Abstract: Predatory mites can be safely released 6 days after spinosad is applied for the management of F. occidentalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…High Araneus pretensis (Emerton) mortality was observed owing to the ingestion of prey treated with low spinosad rates (2.5–25% of the maximum recommended field rates) 53. Risk assessment on predatory mites revealed that the survival of some species belonging to the genera Hypoaspis, Neoseiulus, Typhlodromus and Typhlodromips was significantly affected by contact with dried spinosad residues on leaves (see supporting information Table S1) 54–57. In addition, Rahman et al 57 showed, in a more realistic experimental set‐up, the synergic lethal effect from the exposure to residues and ingestion of prey previously fed on treated leaves.…”
Section: Side Effects Of Spinosyns On Non Target Organisms Reported mentioning
confidence: 99%
See 1 more Smart Citation
“…High Araneus pretensis (Emerton) mortality was observed owing to the ingestion of prey treated with low spinosad rates (2.5–25% of the maximum recommended field rates) 53. Risk assessment on predatory mites revealed that the survival of some species belonging to the genera Hypoaspis, Neoseiulus, Typhlodromus and Typhlodromips was significantly affected by contact with dried spinosad residues on leaves (see supporting information Table S1) 54–57. In addition, Rahman et al 57 showed, in a more realistic experimental set‐up, the synergic lethal effect from the exposure to residues and ingestion of prey previously fed on treated leaves.…”
Section: Side Effects Of Spinosyns On Non Target Organisms Reported mentioning
confidence: 99%
“…Risk assessment on predatory mites revealed that the survival of some species belonging to the genera Hypoaspis, Neoseiulus, Typhlodromus and Typhlodromips was significantly affected by contact with dried spinosad residues on leaves (see supporting information Table S1) 54–57. In addition, Rahman et al 57 showed, in a more realistic experimental set‐up, the synergic lethal effect from the exposure to residues and ingestion of prey previously fed on treated leaves. The new, semi‐synthetic spinosyn spinetoram was also very toxic when applied on eggs and larvae of the western predatory mite Galendromus occidentalis (Nesbitt), while 100% mortality of females was recorded after 72 h of exposure.…”
Section: Side Effects Of Spinosyns On Non Target Organisms Reported mentioning
confidence: 99%
“…The adoption of thresholds for timing insecticide treatments is likely to reduce the selection pressure for resistance and therefore maintain or improve the efficacy of insecticides (Denholm and Jespersen 1998), as well as reducing the side-effects on natural enemies (Rahman et al 2011). Most thresholds developed for strawberry crops are based on assessment of thrips density in flowers, as there is a strong correlation between numbers of F. occidentalis per flower and fruit damage (Steiner and Goodwin 2005b; Coll et al 2007; Sampson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported that these species effectively reduced F. occidentalis numbers in strawberry grown under controlled conditions (Rahman et al., 2011a). Moreover, multiple‐species releases of these predatory mites are more effective than single‐species releases (Rahman et al., 2011b). However, these studies were carried out in controlled environments (25 ± 2 °C, 50–60% r.h.), but the use of these predatory mites in semi‐field protected crops such as low tunnel (floating cover) in relatively cooler condition (<20 °C) is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The biopesticide spinosad is very effective against F. occidentalis in a range of crops including strawberry (Steiner & Medhurst, 2003; Broughton & Herron, 2009b). In our previous studies, we reported that spinosad application followed by releases of predatory mites in two‐ or three‐species combinations is the most effective in controlling F. occidentalis (Rahman et al., 2011b). We also reported that spinosad has no detrimental effects on predatory mites if released 5–6 days post‐treatment (Rahman et al., 2011c).…”
Section: Introductionmentioning
confidence: 99%